#1**+5 **

The first two terms have 5x^{2} in common and the last two terms have 2 in common, so:

10x^{3} + 15x^{2} + 4x + 6 → 5x^{2}(2x + 3) + 2(2x + 3)

Now 2x + 3 appears twice so we can go further and write

10x^{3} + 15x^{2} + 4x + 6 → 5x^{2}(2x + 3) + 2(2x + 3) → (2x + 3)(5x^{2} + 2)

.

Alan
May 7, 2015

#1**+5 **

Best Answer

The first two terms have 5x^{2} in common and the last two terms have 2 in common, so:

10x^{3} + 15x^{2} + 4x + 6 → 5x^{2}(2x + 3) + 2(2x + 3)

Now 2x + 3 appears twice so we can go further and write

10x^{3} + 15x^{2} + 4x + 6 → 5x^{2}(2x + 3) + 2(2x + 3) → (2x + 3)(5x^{2} + 2)

.

Alan
May 7, 2015